2007
DOI: 10.1111/j.1365-3121.2007.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

Passage through India: the Mozambique Ocean suture, high‐pressure granulites and the Palghat‐Cauvery shear zone system

Abstract: The Mozambique Ocean closed as Gondwana formed. Its suture has been identified in Madagascar (Betsimisaraka suture), but its continuation, into India, is controversial. The Palghat-Cauvery shear system appears an ideal candidate as it: (i) lies along strike of the Betsimisaraka suture in Gondwana; (ii) forms a high-pressure granulite belt; and (iii) separates crustal domains with different geological histories. However, existing age constraints have been used to suggest that the structure is Archaean/Palaeopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
135
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 240 publications
(155 citation statements)
references
References 48 publications
11
135
1
Order By: Relevance
“…A Cambrian age is confirmed by 0.52 Ga monazite included in staurolite and kyanite (Maxwell et al, 2014), consistent with high-strain rocks west of the Masora Domain that record metamorphic ages of 0.56-0.52 Ga and an eastwards P increase from 0.7-1.0 GPa and 700-750°C to 1.0-1.2 GPa and 600-650°C . A similar picture emerges in India, where the Palghat-Cauvery shear zone contains kyanite schist with peak conditions of 0.9-1.2 GPa and 750-850°C at 0.53-0.51 Ga followed by decompression along a clockwise P-T path (Collins et al, 2007a;Clark et al, 2009;Raith et al, 2010;Santosh et al, 2012). Collins et al (2007a) and Clark et al (2009) argued for T > 900°C during decompression, but conservative estimates imply maximum T of 800-850°C (Sengupta et al, 2009;Raith et al, 2010).…”
Section: Metamorphism Along the Malagasy Suturementioning
confidence: 83%
See 2 more Smart Citations
“…A Cambrian age is confirmed by 0.52 Ga monazite included in staurolite and kyanite (Maxwell et al, 2014), consistent with high-strain rocks west of the Masora Domain that record metamorphic ages of 0.56-0.52 Ga and an eastwards P increase from 0.7-1.0 GPa and 700-750°C to 1.0-1.2 GPa and 600-650°C . A similar picture emerges in India, where the Palghat-Cauvery shear zone contains kyanite schist with peak conditions of 0.9-1.2 GPa and 750-850°C at 0.53-0.51 Ga followed by decompression along a clockwise P-T path (Collins et al, 2007a;Clark et al, 2009;Raith et al, 2010;Santosh et al, 2012). Collins et al (2007a) and Clark et al (2009) argued for T > 900°C during decompression, but conservative estimates imply maximum T of 800-850°C (Sengupta et al, 2009;Raith et al, 2010).…”
Section: Metamorphism Along the Malagasy Suturementioning
confidence: 83%
“…) and clockwise P-T path was assumed to date ocean closure and collision with the Dharwar Craton (Collins et al, 2007a;Clark et al, 2009Clark et al, , 2015. Although this model of western and eastern collisions at~0.65 and~0.53 Ga explains protracted Pan-African metamorphism, it has a number of problems including the 170 Myr gap from the end of continental arc magmatism at~0.70 Ga to ocean closure along the Malagasy suture, and the observation that Dharwar-like basement of the Masora Domain is overlain by supracrustal rocks with 2.2-1.8 Ga detritus and intruded by 0.85-0.78 Ga granite and gabbro Tucker et al, 2011a), both of which should only occur west of the Malagasy suture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AnatolideTauride Block and Central Anatolian Crystalline Complex, constituted a part of the northern margin of Gondwana, probably in a position close to that of Arabia (Candan et al, in press;Gessner, Collins, Ring, & GUngOr, 2004;Kröner & Stern, 2004;Linnemann, D'Lemos et al, 2009;Linnemann, McNaughton et al, (Candan et al, in press). The possible locality of the suture zone in the India-Madagascar and northward continuity beneath the Phanerozoic cover of Arabia are after Collins et al (2007) and Allen (2007). Granulite localities (red diamonds) in East African Orogen are after (1) Coolen, Priem, Verdurmen, and Verschure (1982), (2) Maboko and Nakamura (1996) and Muhongo, Kröner, and Nemchin (2001), (3) Kroner et al (1997), (4) Macey et al (2013), (5) Möller , Mezger, and Schenk (2000), (6) Jöns and Schenk (2008), (7) Hauzenberger et al (2007), (8) and Collins, Clark, and Plavsa (2014); (9) Pant et al (2013), (10) Adachi et al (2013) and (11) Hokada et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…Kröner et al (2015) reported that granitic rocks of the Trivandrum and Nagercoil Blocks were emplaced between 2100-1750 Ma and were intercalated with metasedimentary rocks that must have been older than 2100 Ma. However, Collins et al (2007) and Taylor et al (2014) reported 1800-1700 Ma detrital zircon ages from metasedimentary rocks of the Trivandrum Block, indicating that the sedimentary protoliths must be~1800 Ma or younger. Therefore, more studies are required to understand the detailed provenance history of metasediments in the Trivandrum Block.…”
Section: Geochronological Constraints From Other Gondwana Fragmentsmentioning
confidence: 99%